Sistem Pendukung Keputusan Kelayakan Sertifikasi Guru Menggunakan Metode Additive Ratio Assessment (ARAS) - Irman Wati Zai (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The implementation of teacher certification is the government's commitment to implement the mandate of Law Number 14 of 2005, namely to create qualified and professional teachers. At SMA N. 1 Lahewa matters related to the certification process are still not subjective. To be able to take the teacher certification test and pass it is not easy. Educators must go through several stages and procedures that must be followed by each participant. Therefore, to solve this problem, the authors chose to solve it by creating a decision support system using the Additive Ratio Assessment (ARAS) method. SPK is an interactive information system that provides information, modeling and data manipulation. The ARAS method is used to compare the overall index value of each alternative to the optimal alternative overall index value. This research produces a decision support system that can recommend teachers who are eligible to take teacher certification at SMA N. 1 Lahewa based on criteria using the ARAS method. A trial was carried out by entering a data sample of 10 teacher data at SMA N. 1 Lahewa. The existence of a decision support system can provide recommendations for teachers who are eligible to take part in the certification process based on ranking.